Upaya Meningkatkan Kepedulian Masyarakat terhadap Lingkungan melalui Pembuatan Bak Sampah di Desa Lewolaga - Donata Peni; Mariana Marta Towe (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
Environmental cleanliness is an important aspect in supporting the quality of life of the community, one of which is influenced by the availability of adequate waste management facilities. The problem faced by the community in Lewolaga Village, East Flores Regency is the limited waste disposal facilities so that the habit of littering still often occurs. This activity aims to provide trash bins and increase public awareness in maintaining environmental cleanliness. The implementation method includes the stages of observation, planning, implementation, socialization and handover. The activity took place in April 2026 with the local community. The results of the activity show that the presence of trash bins makes it easier for the community to manage waste and contributes to improving environmental cleanliness. In addition, counseling regarding the sorting of organic and non-organic waste can increase understanding and shape community behavior to be more orderly in disposing of waste. Overall, this program has a positive impact in creating a clean and healthy environment.